1954
DOI: 10.1111/j.1440-1819.1954.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Amygdaloid Nuclei and Periamygdaloid Cortex With Special Reference to Its Effects on Uterine Movements and Ovulation

Abstract: Summary A series of experiments was performed in an attempt to establish the anatomical localization of the effects upon uterine movements and ovulation due to the stimulation of the amygdaloid complex. A remarkable change in the uterine movements was recognized through electrical or chemical stimulation of delimitd parts of the amygdaloid nuclei in dogs, cats and rabbits. In pxtpartum and in non‐pregnant matured animals, as well as in the latter half of pregnancy, an increase of tonus in uterine musculature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
1
2

Year Published

1957
1957
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 83 publications
2
16
1
2
Order By: Relevance
“…Our present results clarified that the origins of the amygdalofugal fibers to the preoptic area are phylogenetically older portions of the amygdaloid complex. We also partially proved that the corticomedial group of the amygdaloid complex was concerned with ovulation (13,14), but the cortical and basal nuclei which Koikegami (13,14) stimulated in order to observe ovulation in 1954 showed no positive reaction in the present study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our present results clarified that the origins of the amygdalofugal fibers to the preoptic area are phylogenetically older portions of the amygdaloid complex. We also partially proved that the corticomedial group of the amygdaloid complex was concerned with ovulation (13,14), but the cortical and basal nuclei which Koikegami (13,14) stimulated in order to observe ovulation in 1954 showed no positive reaction in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…The significant role of the amygdaloid complex in the release of gonadotropin has been studied by several investigators (4,7,12,16,23), and it is generally accepted that the impulses from the amygdaloid complex which trigger ovulation (3,13,14) may be transmitted to the preoptic area (10, 24) passing through the stria terminalis (25), and accelerating the release of LH-RH (11) which is mainly produced in the neurons in the preoptic area (2).…”
mentioning
confidence: 99%
“…The amygdala can be divided into two cytoarchitectonically distinct functional divisions, corticomedial and basolateral, which exert opposing modulatory influences on the hypothalamus by largely separate outflow tracts, the stria terminalis and the ventral amygdalofugal pathway (24). For example, stimulation of the corticomedial amygdala can induce ovulation and uterine contraction (25,26). Transection of the stria blocks this ovulatory response, whereas lesion of the ventral amygdalofugal pathway does not (26).…”
Section: Discussionmentioning
confidence: 99%
“…and a half on the hypothalamus as well as on the limbic system. (Koikegami et al, 1954;Kawakami et al, 1967). Many studies concerned with gonadal function and the mechanism of ovulation have been reported in relation to these two areas, and consequently the electrophysiological activity of each area, independently, has been clarified to some extent.…”
mentioning
confidence: 99%